The Effectiveness Of Sound Effects As A Supplement In An Industrial Product (Journal of the College of Basic Education, 2024)
The first chapter dealt with the research problem, which was concerned with the identification of the sound effect and its active role as an influencer in industrial products, as well as its role as a functional and aesthetic complement, this is in addition to that it is the language of dialogue between the designer as a sender and between the product as a message and the recipient as a recipient where the sound effects work in reviving the process of communication and communication between Product and receiver. Today it has become one of the functional and aesthetic supplements of the product, which has become the concern of the designer, in how it is introduced to the product and its exploitation of aesthetic and functional expression. Hence the question: - Awi. What is the effect of sound on the industrial product as a functional and aesthetic supplement? As for the importance of the research, it came to raise awareness of the role of sound effects in achieving the aesthetic, functional and utilitarian aspects of users of these products. The research aims to know: What is the role of the sound effect as a functional and expressive aesthetic supplement in the industrial product? As well as dealing with some terms related to research. The second chapter discussed sound and learned about sound effects in the industry, which is one of the reasons that work to increase the factors of attraction, suspense, and entertainment. His natural influence arose for the types of star voices, which include actors, industrial ones, and another axis, which is vocal performance as a complement to the aesthetic and expressive performance. I investigated the intentional eye in the third chapter of the research, and the Samsung products scheduled for 2019 were taken as a sample group and were analyzed using descriptive analysis. The end of the search for results, the search for results, the most important of which was the sound effect, its voice, a dialogue between the recipient and the design product, through which the audience conveys the meaning, content, and message in a way that is more easy, convincing, accepting, and simple